Comparative mydriatic study: tropicamide vs. biosimilar in normal and diabetic patients with quality control analysis - Farooqui, Fareena; Sohaib Zafar Malik (Journal of the Pakistan Medical Association, 2025)
Objective: To compare the effectiveness of tropicamide and its biosimilar drug in normal and diabetic patients. Method: The prospective cohort study was conducted at Amanat Eye Hospital on March 5, 2023 to 5 December, 2023, and comprised individuals aged 40-50 years. Diabetic patients formed group A, while healthy controls were in group B. Tropicamide 1% was used for mydriasis in the left eye of all the subjects, and a biosimilar drug was used for mydriasis in the right eye. After administration, the size of the pupil was analysed. Data was analysed using Paired t-tests for continuous variables and McNemar’s test for categorical variables. Results: Of the 300 subjects (150 males, 150 females), 150(50%) were in each of the two groups. In group B, 29(19.33%) eyes were perfectly dilated in response to tropicamide compared to 23(15.43%) with biosimilar drug. In group A, the corresponding values were 53(35.33%) and 25(16.66%), respectively. Conclusion: Tropicamide was found to be more effective compared to its biosimilar drug. Besides, tropicamide was more effective in healthy individuals compared to diabetic individuals. Key Words: Tropicamide, Biosimilar drug, Diabetic.